2021
DOI: 10.1097/wnp.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Findings in Critical COVID-19 Patients With Peripheral Nervous System Manifestations

Abstract: Introduction:Coronavirus disease 2019 patients hospitalized in intensive care units develop neuromuscular manifestations. However, to our knowledge, a study describing the neurophysiological findings in these patients has not been reported. The objective of this study was to diagnose the cause of neuromuscular deficit in severe coronavirus disease 2019 patients, through neurophysiological examination.Methods:This is a retrospective, observational case series. Data were collected from April 13, 2020, to May 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Hameed et al reported the electro-diagnostic findings of 18 COVID-19 patients, in which the majority were consistent with a myopathy (82%) and 5 of them also had a concurrent axonal neuropathy [ 7 ]. Santiago-Pérez, et al reported the electrophysiological results of 22 COVID-19 patients [ 13 ]. Myopathy was diagnosed in 17 patients (77.3%) and polyneuropathy in 4 (18.2%).…”
Section: Introductionmentioning
confidence: 99%
“…Hameed et al reported the electro-diagnostic findings of 18 COVID-19 patients, in which the majority were consistent with a myopathy (82%) and 5 of them also had a concurrent axonal neuropathy [ 7 ]. Santiago-Pérez, et al reported the electrophysiological results of 22 COVID-19 patients [ 13 ]. Myopathy was diagnosed in 17 patients (77.3%) and polyneuropathy in 4 (18.2%).…”
Section: Introductionmentioning
confidence: 99%